2023
DOI: 10.2147/prbm.s412013
|View full text |Cite
|
Sign up to set email alerts
|

Depressive and Anxious Symptoms Increase with Problematic Technologies Use Among Adults: The Effects of Personal Factors Related to Health Behavior

Abstract: Background Depression and anxiety disorders are a significant and growing health problem that has a significant impact on psychosocial functioning and quality of life. The onset and severity of mental health problems have been related to various biological, psychosocial, and behavioral variables. Purpose The purpose of this study was to explore the association among the severity of depression and anxiety, problematic information and communications technology (ICT) use, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Many parents have perceived physical punishment and strict parenting as manifestations of care and affection, as evidenced by the proverb, ‘beating and scolding represent love’ [ 31 ]. Studies have shown that individuals who experienced childhood trauma tended to feel less parent affection, exhibited poorer self-esteem and self-worth, and were more prone to developing IGD as a coping mechanism for loneliness and being loved [ 32 , 33 ]. In addition, numerous studies have revealed that childhood trauma impaired neuroplasticity and neurogenesis in brain circuits that regulated emotion and motivation, which was the biological basis for susceptibility to addictive behaviours [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many parents have perceived physical punishment and strict parenting as manifestations of care and affection, as evidenced by the proverb, ‘beating and scolding represent love’ [ 31 ]. Studies have shown that individuals who experienced childhood trauma tended to feel less parent affection, exhibited poorer self-esteem and self-worth, and were more prone to developing IGD as a coping mechanism for loneliness and being loved [ 32 , 33 ]. In addition, numerous studies have revealed that childhood trauma impaired neuroplasticity and neurogenesis in brain circuits that regulated emotion and motivation, which was the biological basis for susceptibility to addictive behaviours [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%